From Syncretism to Indigenous Monotheism: Continuity and Change of Islam Langkah Lama among the Talang Mamak People - Rifqi Nurdiansyah (Indigenous Southeast Asian and Ethnic Studies, 2026)
Studies on local Islamic practices often rely on the colonial terminology of “Syncretic Islam,” assuming indigenous beliefs originated from animism, dynamism, or derivative forms of Buddhism and Hinduism, frameworks that frequently overlook the theological depth of local traditions. This study presents alternative evidence from Islam Langkah Lama, the distinctive Islamic tradition of the Talang Mamak people, arguing that their belief system is better understood as “Indigenous Monotheism,” bearing significant affinity with the Sufi doctrine of Waḥdat al-Wujūd (unity of existence), as evident through theological resonances found in the Kitab Barencong. Based on six months of fieldwork in Bukit Tiga Puluh National Park, the article analyses continuity and change within this tradition, showing that despite prolonged Islamisation and Catholicisation, Islam Langkah Lama has become deeply embedded within customary law (adat), providing a resilient foundation that enables its persistence even as members shift towards orthodox sharia or convert to Catholicism, highlighting both the enduring strength of local religious identity and the complex negotiations faced by indigenous communities in a changing religious landscape.